The opening of John's narrative (John 1:19-2:22) historical, literary, and theological readings from the Colloquium Ioanneum 2015 in Ephesus - Culpepper, R. Alan 1946-; Frey, Jörg 1962-; Colloquium Ioanneum 2015 Selçuk (Tübingen Mohr Siebeck, 2017)
"The essays in this volume provide significant insights into both the Gospel and current Johannine scholarship. The beginning of John's narrative presents interpreters with tantalizing issues. The elusive narrator introduces the witness of the Baptist, then leaves the scene. What is the function of the Isaianic quotation? What is the role of purification in John, the identity of the unnamed disciple, the meaning of the title, "the lamb of God," the "greater things" Jesus promises the disciples will see, the role of the ascending and descending angels, or Jesus' curt response to his mother? These essays also illustrate how, while the Gospel creatively develops and recasts traditional material, it also calls for its readers to actively engage in dialogue with the text." --
Temple violation : reading John 2:13-22 at the Temple of Artemis in Ephesus R. Alan Culpepper.
Literaturverzeichnis: Seite 317-344
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Konferenzschrift -- 2015 -- Ephesus